Theoretical Foundations of Work-Based Learning in Vocational Education: A Narrative Literature Review (2021–2025) - Budiyanto Budiyanto; Tri Wrahatnolo; Heru Arizal; Achmad Imam Agung (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
Studies on Work-Based Learning (WBL) in vocational education published during 2021–2025 demonstrate rapid growth, reflecting the increasing demand for graduates equipped with technical competence, adaptability, and employability skills. However, WBL implementation remains largely focused on workplace practice, while reflective learning, authentic assessment, digital technology integration, and supportive policy frameworks have yet to be systematically embedded. This study aims to identify, map, and analyze the theoretical foundations of Work-Based Learning in vocational education through a Narrative Literature Review. The review examined 14 journal articles published between 2021 and 2025 and retrieved from the Scopus and Google Scholar databases using structured inclusion and exclusion criteria. The synthesis identified five major themes: competency and employability development, supervision and assessment, education–industry collaboration, technology and gamification integration, and discipline-specific pedagogy. The findings indicate that WBL has expanded considerably; however, its implementation is constrained by fragmented instructional design, limited authentic assessment, and insufficient policy support for sustainable education–industry collaboration. WBL effectiveness depends on authentic workplace experiences, reflective learning, effective supervision, authentic assessment, and strong industry partnerships. These findings provide both a conceptual foundation and practical implications for vocational education policymakers to strengthen WBL implementation standards, enhance industry collaboration, and accelerate digital technology integration into vocational curricula.